METODE ITERASI TIGA LANGKAH DENGAN ORDE KONVERGENSI LIMA UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR BERAKAR GANDA - Zuhnia Lega; Agusni '; Supriadi Putra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the three-step iterative method free from derivatives, modied from Newton's three-step method that contains two derivatives, to nd a multiple root of a nonlinear equation with unknown multiplicity. This iterative method has fth order of convergence and for each iteration, it requires four function evaluations, so the eciency index of the method is 1.495. Furthermore, the computational test shows that the discussed method is better than the comparison method when the success of this method is seen in getting estimated roots.